Một số khái niệm của các hệ tìm kiếm và lưu trữ thông tin - Tường, Nguyễn Bá (Journal of Computer Science and Cybernetics, 2016)
In this paper we describe a information system which is some different from previous definition. Problems connected with describing objects by means of an appropriate language of sets as well as efficient methods in the memory of a computer are considered. Areas for further studies are also suggested.